FRI0679 High sensitivity cardiac troponin t in psoriatic arthritis patients: a cross-sectional controlled study. (12th June 2018) - Furer, V.; Shenhar-Tsarfaty, S.; Berliner, S.; Arad, U.; Paran, D.; Rogowski, O.; Shapira, I.; Matz, H.; Elkayam, O.
Abstract : Background: High sensitivity cardiac troponin (hs-cTnT) is a biomarker for cardiovascular disease (CVD) in the general population. (1) Psoriatic arthritis (PsA) confers an increased risk for CVD (2) but there are no biological markers to stratify CVD risk in PsA patients. Objectives: To determine the level of serum hs-cTnT in a PsA cohort and controls without inflammatory disease, and further characterize the PsA cohort with detectable hs-cTnT. Methods: Serum hs-cTnT level was measured with a sandwich immunoassay method in a consecutive PsA cohort (n=96). The control cohort was based on apparently healthy individuals recruited during routine annual health examination, Tel-Aviv Medical Center Inflammatory Survey (TAMCIS) (n=6, 052). hs-cTnT was measured in carefully matched controls (n=88), manually selected from the TAMCIS, based on gender, age, BMI, hypertension, and hyperlipidemia prevalence. Hs-cTnT ≥5 ng/L was used as a cutoff for the detectable level. Multiple regression analysis was used to determine the factors associated with hs-cTnT. Results: The characteristics of the PsA cohort are presented in table 1. Remarkably, in the majority of patients, both skin and joint disease were well controlled. PsA and TAMCIS cohorts had a similar range of age (51.5 vs 48 yr) but different gender representation: 47% vs 72.5% of males (p<0.001). PsA exhibited a higher prevalence of traditional CVD risk factors compared to the TAMCIS cohort: BMI 28 vs 26.5 (p=0.002), current smokers 20.8% vs 10.1% (p=0.002), hypertension 25% vs 15% (p=0.007), dyslipidemia prevalence 34% vs 27% (p= 0.101), diabetes 19.8% vs 4.6% (p<0.0001). Due to these differences, a matched control group was used for comparison of troponin. Detectable hs-cTnT was present in 29.5% of the PsA patients compared to 19.3% in the controls. (p=0.114) Factors associated with detectable hs-cTnT in PsA were consistent with traditional factors and included male gender (p=0.007), age (p=0.005), hypertension (p<0.001), and DM (p<0.001). No correlation between detectable hs-cTnT level and psoriasis/PsA duration, disease severity, treatment with DMARDs or biologics was found. Conclusions: This is the first study to report a detectable hs-cTnT level in up to 30% in patients with well controlled PsA, asymptomatic for CVD, warranting a special attention to monitoring CVD risk factors and manifestations in this group. Traditional CVD risk factors but not measures of disease activity were associated with detectable hs-cTnT. The latter may be explained by a potential positive impact of anti-rheumatic therapies on the cardiovascular profile. Further prospective studies addressing the predictive role of hs-cTnT for CVD events in PsA are needed. References: 1. Saunders JT, et al. Circulation2011;123. 2. Ogdie A, et al. Ann Rheum Dis2015;74. Disclosure of Interest: None declared